Oncostatin M Receptor Type II Knockout Mitigates Inflammation and Improves Survival from Sepsis in Mice - Saad Y. Salim; Nour AlMalki; Kimberly F. Macala; Alyssa Wiedemeyer; Thomas F. Mueller; Thomas A. Churchill; Stephane L. Bourque; Rachel G. Khadaroo (Biomedicines, 2023)
Sepsis remains one of the leading causes of death worldwide. Oncostatin M (OSM), an interleukin (IL)-6 family cytokine, can be found at high levels in septic patients. However, little is known about its role in sepsis. This study aimed to determine if the genetic knockout of OSM receptor (OSMR) type II signaling would improve survival in a murine model of sepsis. Aged (>50 weeks) OSMR type II knockout (KO) mice and wild-type (WT) littermates received an intraperitoneal injection of fecal slurry (FS) or vehicle. The KO mice had better survival 48 h after the injection of FS than the WT mice (p = 0.005). Eighteen hours post-FS injection, the KO mice had reduced peritoneal, serum, and tissue cytokine levels (including IL-1β, IL-6, TNFα, KG/GRO, and IL-10) compared to the WT mice (p < 0.001 for all). Flow cytometry revealed decreased recruitment of CD11b+ F4/80+ Ly6chigh+ macrophages in the peritoneum of KO mice compared to WT mice (34 ± 6 vs. 4 ± 3%, PInt = 0.005). Isolated peritoneal macrophages from aged KO mice had better live E. coli killing capacity than those from WT mice (p < 0.001). Peritoneal lavage revealed greater bacterial counts in KO mice than in WT mice (KO: 305 ± 22 vs. 116 ± 6 CFU (×109)/mL; p < 0.001). In summary, deficiency in OSMR type II receptor signaling provided a survival benefit in the progression of sepsis. This coincided with reduced serum levels of pro-inflammatory (IL-1β, TNFα, and KC/GRO) and anti-inflammatory markers (IL-10), increased bacterial killing ability of macrophages, and reduced macrophage infiltration into to site of infection.